A longitudinal study of upper secondary school students' values and beliefs regarding policy responses to climate change. Issue 5 (4th May 2019) - Ignell, Caroline; Davies, Peter; Lundholm, Cecilia
Abstract: This article explores changes of environmental values and beliefs among secondary school business and economics students regarding government and market solutions to climate change. The quantitative study is longitudinal and a survey was administrated to students at two occasions including 212 participants in the first measurement. Results show a small significant increase in importance for altruistic, biospheric and egoistic value orientations at average. At an individual level, there are substantial movements over time. Nearly two-thirds of the students changed the strength of their value orientations over time. Taxes and legislation were regarded as the most effective solutions to climate change, however there was a decrease in seeing market prices as important mechanisms for change. Analysis suggested no direct relationship between change in environmental value orientation and change in norms. However indirect associations were mediated by changing beliefs in the efficacy of education and information and the efficacy of tax policies. For example, students who became more egoistic and more convinced about the efficacy of tax were less likely than others to be willing to take personal actions.